International Pediatric Otolaryngology group (IPOG) consensus on the diagnosis and management of pediatric obstructive sleep apnea (OSA). (November 2020) - Benedek, Pálma; Balakrishnan, Karthik; Cunningham, Michael J.; Friedman, Norman R.; Goudy, Steven L.; Ishman, Stacey L.; Katona, Gábor; Kirkham, Erin M.; Lam, Derek J.; Leboulanger, Nicolas; Lee, Gi Soo; Le Treut, Claire; et al.
Abstract: Objective: To develop an expert-based consensus of recommendations for the diagnosis and management of pediatric obstructive sleep apnea. Methods: A two-iterative Delphi method questionnaire was used to formulate expert recommendations by the members of the International Pediatric Otolaryngology Group (IPOG). Results: Twenty-six members completed the survey. Consensus recommendations (>90% agreement) are formulated for 15 different items related to the clinical evaluation, diagnosis, treatment, postoperative management and follow-up of children with OSA. Conclusion: The recommendations formulated in this IPOG consensus statement may be used along with existing clinical practice guidelines to improve the quality of care and to reduce variation in care for children with OSA.